Temporomandibular joint magnetic resonance imaging findings in adolescents with anterior disk displacement compared to those with juvenile idiopathic arthritis. (8th October 2018) - Kellenberger, Christian J.; Bucheli, Jeannine; Schroeder‐Kohler, Silke; Saurenmann, Rotraud K.; Colombo, Vera; Ettlin, Dominik A.
Summary: Background: Deformation of the mandibular condyle can be associated with anterior disk displacement (ADD) or involvement of the temporomandibular joint (TMJ) by juvenile idiopathic arthritis (JIA). Diagnostic differentiation is critical for proper management. Objectives: To compare morphology and inflammation between TMJs with ADD and JIA. Methods: Retrospective assessment of contrast‐enhanced TMJ MRI in 18 adolescents (15 female, mean age 15.1 ± 1.9 years) with ADD and age‐ and gender‐matched patients with JIA. Articular disk findings, inflammatory signs and osseous morphology were compared. Results: In the ADD group, 31 of 36 disks were displaced. In total, 28 of 31 displaced disks showed thickening of the bilaminar zone. In JIA patients, the disks were mainly flattened (19/36), centrally perforated (12/36) and/or anteriorly displaced (2/36). In total, 19 of 31 TMJs with ADD showed various degrees of inflammation, with joint effusion, synovial thickening and joint enhancement not significantly different from JIA patients. Osseous deformity was present in 27 of 31 TMJs with ADD, with frequent erosions in both groups (ADD 25/31; JIA 32/36, P = 0.55) but lower grades of condylar and temporal bone flattening than in JIA ( P ≤ 0.001). Glenoid fossa depth was preserved in 28 of 31 joints with ADD and decreased in 26 of 36 joints with JIA ( P < 0.0001). Mandibular ramus height was decreased in both groups. Conclusion: In adolescents, inflammatory signs are common MRI findings in symptomatic TMJs with ADD and thus should not be considered diagnostic for JIA involvement. In this cohort, both entities had high rates of condylar deformity, while TMJs with ADD showed a better‐preserved and often normal shape of the glenoid fossa.